LEGAL CONSTRUCTION OF MARRIAGE REGISTRATION LAW AS AN ADDITIONAL PILLAR FROM THE PERSPECTIVE OF MAQASID ASY-SYARI’AH OF JAMALUDDIN ATHIYAH - Wisnu Indradi; Kamsi Kamsi; Yusdani Yusdani (Universitas Nurul Jadid, 2025)
Marriage is a bond of misaqan galizan between a man and a woman to buidl a happy and eternal family or household based on the Almighty God. Article 1 of Law No. 1 of 1974 concerning Marriage explains the validity of a marriage and the obligation to register a marriage. The law of marriage registration has never been discussed before in classical jurisprudence (Fiqh). The marriage registration law is a legal breakthrough to protect rights in the household. Considering the urgency of the marriage registration law, which is so great, then what is the legal position of marriage registration in a marriage. There are two questions in this study: 1.) What is the law on marriage registration according to the perspective of Jamaluddin Athiyah’s maqasid asy-syari’ah and 2.) How is the reconstruction of the law on marriage registration in Indonesia into an additional pillar in marriage?. This study concludes that: First, the law of marriage registration has been in accordance with the concept of maqasid asy-syari’ah developed by Jamaluddin Athiyyah as marriage registration has fulfilled seven objectives as stated in maqasid asy-syari’ah within the family scope. Second, the concept of marriage registration is a form of reactualization of the position of witnesses in marriage. Thus, the researcher places marriage registration as an additional pillar in the marriage procession that has an equal position as witnesses.